Sonographic assessment of pediatric chest wall thickness and width of the intercostal space: correlation with anthropometric data and implications for needle decompression - Terboven, Tom; Betka, Ivette; Weiß, Christel; Rudolph, Marcus; Viergutz, Tim; Leonhard, Georg; Schöler, Michael (The ultrasound journal, 2021)
Emergent needle decompression in children is a rare event for emergency medicine and critical care providers. Hereby, risk of injury of intrathoracic structures is high and knowledge of age-specific values of chest wall thickness and width of the intercostal space (ICS) is crucial to avoid injuries. Investigation of the correlation of chest wall thickness and width of the intercostal space with age and body dimension like weight and height could provide guidance on depth of insertion and choice of the needle.